2018
DOI: 10.1186/s12942-018-0149-5
|View full text |Cite
|
Sign up to set email alerts
|

Capturing exposure in environmental health research: challenges and opportunities of different activity space models

Abstract: BackgroundThe built environment health promotion has attracted notable attention across a wide spectrum of health-related research over the past decade. However, the results about the contextual effects on health and PA are highly heterogeneous. The discrepancies between the results can potentially be partly explained by the diverse use of different spatial units of analysis in assessing individuals’ exposure to various environment characteristics. This study investigated whether different residential and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 60 publications
(119 reference statements)
3
72
2
2
Order By: Relevance
“…The validity of the use of commonly used buffers to account for the effect of built environment on individuals' travel behavior has, therefore, become controversial (e.g. Perchoux et al 2013;Holliday et al 2017;Laatikainen et al 2018). Such predefined spatial units of analysis have been criticized for not being able to define the spatiotemporal extents of individuals' neighborhoods and spatial exposure (e.g.…”
Section: Research Gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity of the use of commonly used buffers to account for the effect of built environment on individuals' travel behavior has, therefore, become controversial (e.g. Perchoux et al 2013;Holliday et al 2017;Laatikainen et al 2018). Such predefined spatial units of analysis have been criticized for not being able to define the spatiotemporal extents of individuals' neighborhoods and spatial exposure (e.g.…”
Section: Research Gapsmentioning
confidence: 99%
“…Such predefined spatial units of analysis have been criticized for not being able to define the spatiotemporal extents of individuals' neighborhoods and spatial exposure (e.g. Mitra and Buliung 2012;Perchoux et al 2013;Holliday et al 2017;Laatikainen et al 2018). As Hasanzadeh et al (2017) put it, although the use of buffer has priority over the traditionally rigid neighborhood definitions (such as large traffic analysis zones or administrative boundaries), such definition of neighborhood is individual-centered, but not individual specific for the spatial extent of neighborhood is systematically defined in a uniform way for all individuals.…”
Section: Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is been shown that differing spatial measurement methods in built environment research can lead to different results for the same exposure-outcome pair. 307 The results of the current study are similar to results from previous work using a range of spatial measurements, which allows more confidence that the findings have not been unduly influenced by the spatial units available. A further limitation on the use of locality as the spatial unit is that locality boundaries may have changed over the duration of the study, and this cannot be accounted for in this study.…”
Section: Limitationssupporting
confidence: 88%
“…Real-time geolocation data (e.g. those acquired by GPS sensors in smartphones) permit a detailed description for activity spaces for equipped individuals [26], but the complexity of these analyses [27][28][29][30] calls for a simplified approach for public health studies.…”
Section: Discussionmentioning
confidence: 99%